Angiotensin receptor blockade mediated amelioration of mucopolysaccharidosis type I cardiac and craniofacial pathology. Issue 2 (14th October 2016) - Osborn, Mark J.; Webber, Beau R.; McElmurry, Ronald T.; Rudser, Kyle D.; DeFeo, Anthony P.; Muradian, Michael; Petryk, Anna; Hallgrimsson, Benedikt; Blazar, Bruce R.; Tolar, Jakub; Braunlin, Elizabeth A.
Abstract: Mucopolysaccharidosis type I (MPS IH) is a lysosomal storage disease (LSD) caused by inactivating mutations to the alpha‐ L ‐iduronidase (IDUA) gene. Treatment focuses on IDUA enzyme replacement and currently employed methods can be non‐uniform in their efficacy particularly for the cardiac and craniofacial pathology. Therefore, we undertook efforts to better define the pathological cascade accounting for treatment refractory manifestations and demonstrate a role for the renin angiotensin system (RAS) using the IDUA −/− mouse model. Perturbation of the RAS in the aorta was more profound in male animals suggesting a causative role in the observed gender dimorphism and angiotensin receptor blockade (ARB) resulted in improved cardiac function. Further, we show the ability of losartan to prevent shortening of the snout, a common craniofacial anomaly in IDUA −/− mice. These data show a key role for the RAS in MPS associated pathology and support the inclusion of losartan as an augmentation to current therapies.